Real Time System Scheduling Approach:Survey - Abdullah, Dhuha; Abood, Israa; hamdi, Raya (AL-Rafidain journal of computer sciences and mathematics, 2023)
Real-time systems play a major role in our today's life. They are used in essential control systems that rely on timely response and determined outcomes to work. The main real-time scheduling algorithms for both soft and hard real-time system is presented in this paper, both in processors uniprocessor and multiprocessor schemes. The effectiveness of scheduling is derived from various factors, including hardware configuration, real-time application type, and real-time problem complexity. This review presents a characterization of scheduling techniques to help the researcher to get enough knowledge in real-time systems with adequate scheduling schemes to reach their timeliness characteristic. In this paper, we aim to investigate the scheduling attributes and scope of research in real-time computing, and classify real-time system in two categories: algorithms for multiprocessor scheduling and algorithms for uniprocessor scheduling. Furthermore, gives special attention to characteristic and their task, that is one of the following original contributions to real-time scheduling algorithms.